Effectiveness of Electric Heaters on Stoves Fueled by Used Oil - Ahmad Farid; Muhammad Agus Shidiq; Galuh Renggani Wilis; Bayu Firman Nursaid (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This research aims to analyze the effectiveness of designing a stoves using used fuel oil, which has the ability to burn faster and produce less smoke. The findings show that used oil becomes more flammable as its temperature increases. Therefore, in this research, an electric heater was added to heat the oil before the oil enters the combustion chamber. The method used in this research was experimental. The experiment involved heating the oil using an electrical system at temperatures of 80°C, 100°C, and 120°C. Each test was conducted three times to calculate the combustion rate, fuel consumption, stove power, and thermal efficiency, using the average results from each experiment. The results indicate that when the stove uses used oil to boil 1 liter of water, the flame temperature varies according to the oil's heating temperature. At 120°C, the flame temperature reaches 530.5°C; at 100°C, it reaches 501.2°C; and at 80°C, it reaches 476.7°C. The highest burning rate was recorded at 7.62 grams per minute, with a cooking time of 5.46 minutes for 1 liter of water at 80°C. At 100°C, the cooking time was 5.30 minutes with a burning rate of 7.57 grams per minute, while at 120°C, the burning rate was 7.50 grams per minute with a cooking time of 5.16 minutes. The shortest boiling time for 1 liter of water was achieved at an oil heating temperature of 120°C, taking 310 seconds. The boiling times at 100°C and 80°C were 318 and 328 seconds, respectively. In terms of fuel consumption, the most efficient operation occurred at 120°C with a consumption of 0.144 ml/s, followed by 100°C at 0.146 ml/s and 80°C at 0.147 ml/s. The maximum power output of the stove when heating 1 liter of water was recorded at 80°C, reaching 48,140.80 Watts. At 100°C, the power produced was 47,353.57 Watts, while at 120°C, it reached 47,212.39 Watts. The highest thermal efficiency was measured at 120°C with a value of 3.33%, followed by 100°C at 3.21% and 80°C at 2.83%.